Analysis on the performance of adsorption route in a tropical region - Wan Nurlisa, Wan Ahmad (2013)
Nowadays, adsorption chiller attracts attention to be used in cooling system in tropical region due to their minimum heat required and environmental friendly characteristics. The objectives in these studies are to study about the stable solar driven cooling system by adsorption route in a tropical region and to study about the performance of cooling system in the tropical region. The complete cooling system flow is starting from the solar intensity, then absorb by the solar plate collector, the energy is directly stored to the storage water tank to be used for the two beds of the adsorption chiller and lastly it will be supplied cooling energy to the residential building. Solar data and residential cooling load in the tropical region are obtained from the journal. In order to get the best performance of cooling system in term of cost and emission produce, there are 3 difference cases that used different component and energy source. By using the storage water tank as a main component to store the energy from the solar plate collector, two auxiliary components are also chosen when the volume of the storage water tank is reduced to 60% and 30% from the original volume, they are electric heater and natural gas boiler. It is another alternative to get higher heat energy in the water storage and they also act as a backup system for the solar plate collector. The best cooling system in term of cost and emission produce is the boiler with 30% reduction of original volume storage water tank which is RM 2355 for the installation and RM15.98 per month for energy cost. While, monthly cost for conventional air-conditioning is RM333.54 that used 55kW for the whole residential building. For the emission produce per month for this case are 33g for CO2, 1.97g for CO, and 3.61g for NOX, it is contrast with conventional air-conditioning which is 1446.56g for CO2 13.63g for CO, and 9.34g for NOX.